Funcionarios Centro de Investigación para el Desarrollo de la Educación a Distancia. (UNED, 2025)
Sentadas: Marlene Víquez, Alejandra Cruz, Patricia Murillo, De pie: Luis Paulino Vargas, Fernando Bolaños, Lucía Herrera, Hernán Pérez y Manuel Mora